2005
DOI: 10.1002/qua.20802
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and spin polarization in quantum dots: Local spin density functional theory revisited

Abstract: ABSTRACT:Using quantum dot artificial atoms as a simple toy model, we reflect on the question of whether spin density functional theory (SDFT) can accurately describe correlation effects in low-dimensional fermion systems. Different expressions for the local density approximation of the exchange-correlation energy for the twodimensional electron gas, such as the much-used functional of Tanatar and Ceperley, and the recent suggestion by Attaccalite et al., are compared with the results of a numerical diagonaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…23,27,36,38,42 We do find many violations of Hund's second rule -the value of the orbital angular momentum is not necessarily a maximum -but a modified second rule holds for small r s . (iv) The addition energy curve first becomes smoother as interactions strengthen -the mesoscopic fluctuations are damped by correlation -and then starts to show features characteristic of the classical addition energy, indicating incipient Wigner crystallization.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…23,27,36,38,42 We do find many violations of Hund's second rule -the value of the orbital angular momentum is not necessarily a maximum -but a modified second rule holds for small r s . (iv) The addition energy curve first becomes smoother as interactions strengthen -the mesoscopic fluctuations are damped by correlation -and then starts to show features characteristic of the classical addition energy, indicating incipient Wigner crystallization.…”
Section: Introductionmentioning
confidence: 79%
“…21 Early calculations using density functional theory (DFT) within the local spin density approximation showed a spin density wave (SDW) signature for r s as small as 2. 22,23 Unrestricted Hartree-Fock (UHF) 24 yielded both SDW and charge density wave (CDW) features for r s ∼ 1. These were initially identified as signatures of strong correlations related to the analog of a WC in a finite system, often called a "Wigner molecule".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27), t c (ρ) and v d ee (ρ) are the kinetic correlation energy and the electron-electron decorrelation energy per particle of an electron gas with uniform density ρ, corresponding to…”
Section: Local Correction To Zeroth-order Ks Scementioning
confidence: 99%
“…Instead, one then has to investigate the pair correlation functions, i.e., conditional probabilities, to study the internal structure [35,36]. Indeed, the direct comparison to spin-dependent pair correlation functions in the configuration interaction method, clearly demonstrated that SDW-like states in question can appear in the internal structure of the exact many-body state [39]. However, the SDFT results remain questionable for the discussion of spin multiplets, as already shown by von Barth in 1979 [33].…”
Section: Two-dimensional Quantum Dots: Dftmentioning
confidence: 99%